Studying the Creation and Characteristics of the Heroes in the Manga version of “Sailor Moon” using Folklore Approach - Piriyothinkul, Thanapat (FOYER: The Journal of Humanities, Social Sciences, and Education, 2021)
This research paper aims to study the prominent characteristics and significance or function of the heroic character of “Sailor Moon” from the 18 volumes of the manga series Sailor Moon published in Thailand using folklore methods and Joseph Campbell's concept of heroes. This study found that “Sailor Moon” manga as a “Heroes Tale”. Sailor Moon's Heroic Journey Model consists of four worlds: past, present, near future, and distant future. It shows two main characteristics of heroism: the relationship between the worlds. And the fulfillment of Sailor Moon's spiritual mission. The prominent motif are a female warrior hero, in the character of the student, and a demigod female hero. Sailor Moon heroism is important in a sociocultural dimension. Both being a role model for life, Reflecting on Japanese nationalist ideology, and its use as a symbol of group identity. This article is an example of the study of cartoons in cultural dimensions and in cross-cultural contexts by using folklore approaches to deepen the understanding of the importance of intercultural cartoons that have spread in Thai society.